To interpret and analyze the changing patterns of histology and direct immunofluorescence findings in membranoproliferative glomerulonephritis - Pragnya P. Nayak; Pranati Pradhan; Dilleswari Pradhan; Nachiketa Mohapatra; Sarojini Raman; Pranabandhu Sahoo (Indian Journal of Pathology and Microbiology)
Background: Membranoproliferative glomerulonephritis has in the recent past been regrouped into immune complex-mediated (ICM MPGN) disease (driven by the classical complement pathway) and complement-mediated (C3GN) disease (driven by the alternative complement pathway) based on pathogenetic role of alternative complement pathway and immunofluorescence deposits. The proposed regrouping lent therapeutic and prognostic support in managing the disease of MPGN. Aims and Objectives: The present study is undertaken to study the patterns of MPGN based on histopathological and DIF examination and sub-categorize the cases into mainly complement dominant and immune complex-mediated diseases for better prognostic and therapeutic utility. Materials and Methods: This is a prospective observational study carried out in a tertiary care center over a period of 2 yrs. The clinically suspected cases of MPGN were subjected to histopathologic and direct immunofluorescence examination (DIF), and the findings were interpreted in light of complement-mediated and immune complex-mediated MPGN. Results: Out of 620 renal biopsies, diagnosis of MPGN was confirmed both on histopathology and DIF in 36 cases accounting for 5.8% of all biopsies. Based on DIF findings, the various groups comprised 20 cases (55.6%) of immune complex deposits, 11 (30.5%) of C3 dominant picture, and 5 (13.9%) of Nil immune deposits. On analysis of the patterns on DIF, 16 cases (80%) of C3 + Ig group and 6 (54.5%) of C3GN group showed predominantly MPGN pattern. Crescentic glomerulonephritis, global glomerulosclerosis, and interstitial fibrosis were markedly observed in C3GN group. Conclusion: DIF is of immense prognostic and therapeutic value in managing cases of MPGN.